Development of a water-in-oil-in-water adjuvant for foot-and-mouth disease vaccine based on ginseng stem-leaf saponins as an immune booster. (August 2020) - Xu, Hai; Niu, Yale; Hong, Weiming; Liu, Weixin; Zuo, Xiaoxin; Bao, Xi; Guo, Changming; Lu, Yu; Deng, Bihua
Highlights: Adjuvant CV13 could prepare stable W/O/W emulsion by one-step emulsification. Adjuvant CV13 containing GSLS had shown a good immune synergistic effect. FMD vaccine prepared with CV13 containing GSLS induced high level of immune response. Abstract: There has been an increasing interest in finding new formulations that qualify as vaccine adjuvants, which must be safe, stable, and have the capacity to stimulate a strong immune response. In this study, a basic formulation of a water-in-oil-in-water (W/O/W) adjuvant CV13 was developed, and ginseng stem-leaf saponins (GSLS) were added as an immune booster into oil phase. The physicochemical properties of the adjuvant were tested. Furthermore, the immune activity and the adjuvant effects, as indicated by the foot-and-mouth disease virus (FMDV) antigen were evaluated. The results showed that CV13 was similar in appearance to ISA 206 and could package FMDV antigen into a stable W/O/W emulsion. The FMD vaccine prepared with CV13 alone or CV13 containing GSLS achieved pharmaceutical characteristics comparable to a vaccine prepared with ISA 206, moreover the structural stability of the CV 13 vaccine was found to be better. Mice that were immunized with the FMD vaccine prepared with CV13 containing GSLS presented a significantly higher LPBE antibody titer and splenocyte proliferation rate than those immunized with a vaccine prepared with CV13 alone (p < 0.05). In addition, there was no significant difference between the groups that were immunized with FMD vaccine prepared with CV13 containing GSLS and ISA206 in terms of cellular and humoral immune response. In this paper, CV13 containing GSLS shows excellent immunologic adjuvant effect in mice model, and this new adjuvant may provide a potential choice for FMD vaccine production in the future.